Immediate and long term effects of endurance and high intensity interval exercise on linear and nonlinear heart rate variability - Perkins, S. E.; Jelinek, H. F.; Al-Aubaidy, H. A.; de Jong, B. (Journal of Science and Medicine in Sport, 2017)
Objectives: Recovery of cardiac autonomic modulation following exercise can be measured using heart rate variability. The objective of this study was to investigate and compare recovery of autonomic cardiac regulation over three days following a single session of high intensity interval training compared to endurance training. Design: Nine untrained students completed two exercise protocols in a one-way crossover design. The endurance protocol consisted of 45 min of moderate intensity cycling, and the high intensity interval protocol of six 30 s sets of high intensity cycling. Methods: Cardiac autonomic activity recovery was measured over three days post-exercise for two hours immediately following each exercise session and each morning thereafter using linear and nonlinear heart rate variability analysis. Results: Both linear and nonlinear measures were significantly decreased immediately following exercise indicating loss of vagal activity. Root mean sum of squared differences (p = 0.031) and high frequency (p = 0.031) were suppressed following the interval exercise only. The long term correlation of the heart rate applying detrended fluctuation analysis was decreased immediately following endurance training (p = 0.039) and trended to increase immediately following the interval protocol (p = 0.156). Sample entropy was decreased immediately following both the endurance (p = 0.023) and interval (p = 0.031) protocols. No exercise effects were noted from 24 h post exercise onwards. Conclusions: High intensity interval training had a greater impact on neurocardiac activity than moderate intensity endurance training as indicated by both linear and nonlinear heart rate variability measures. AUTORREFERAT